Resiliensi Keluarga Dengan Anak Gangguan Disintegratif Melalui Konseling Kelompok - Rahmanawati, Festa Yumpi; Wibowo, Danan Satriyo (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2017)
The purpose of this   research was to explore how families with children with Childhood Disintegrative Disorder (CDD) who participated in group counseling that  were able to move through the adverse situation that they face while raising a child with significant developmental needs and challenges. The theoretical framework that guided this research was family resilience. Qualitative research with case study approach was choosed  to explore families with CDD. Observations and face-to-face interviews were conducted with each of the participants in their own home or in a school setting. The first question research focused on the experience of families who provided beneficial group counseling. Three themes emerged: a) focusing on child-positif behaviour target; b) accepting child in their  ideal image realistically; c) providing motivation in positif parenting practice. The second question research focused on the experience of families who demonstrated willingness to find  family resources after  participated in group counseling. Four themes emerged: a) religious coping; b) positive seeking support; d) gratitude to attainable child competence.Key words: family resilience, disintegrative disorder, group couselling, case study